Implementation of and to and in data security and privacy of the WhatsApp social media application - Tendri Harnovik; T.M.A Azis Alfarisy; Widia Hutapea; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This research explores the implementation of "End-to-End" technology in the context of data security and user privacy on the WhatsApp social media application. "End-to-End" plays a crucial role in maintaining the confidentiality of communications on these platforms, by analyzing the encryption mechanisms used and their impact on the security of user information. This research uses a WhatsApp case study to clarify the effectiveness of this technology in protecting users' personal data from external and internal threats.